Negative electrode material for lithium secondary batteries with improved reversibility and method for producing same

The integration of carbon nanotubes within and outside the negative electrode material for lithium secondary batteries addresses conductivity and structural issues, improving the battery's discharge reversibility and cycle life through enhanced electrical paths and stability.

JP2025500501AActive Publication Date: 2025-01-09CLEANSOLUTION CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024538378
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-12-15
Publication Date
2025-01-09
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

Existing negative electrode materials for lithium secondary batteries, particularly those based on silicon, suffer from volume changes during cycling, low discharge capacity, and inadequate electrical conductivity, leading to performance deterioration and reduced cycle life.

Method used

A negative electrode material comprising nanosilicon, crystalline carbon, and carbon nanotubes is developed, with the carbon nanotubes protruding both inside and outside the material to enhance conductivity and electrical path between particles, using a manufacturing process that includes spray-drying, pressurization, and carbonization to control the nanotube length and distribution.

Benefits of technology

The solution improves discharge reversibility and cycle life of lithium ion batteries by ensuring effective electrical contact and structural stability, thereby enhancing the battery's performance and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500501000001_ABST
    Figure 2025500501000001_ABST
Patent Text Reader

Abstract

The present disclosure provides an anode material for lithium secondary batteries, comprising nanosilicon, crystalline carbon, amorphous carbon and carbon nanotubes, one end of the carbon nanotubes being located inside the anode material and the other end protruding to the outside, and an average length of the carbon nanotubes protruding to the outside of the anode material being in the range of 0.1 μm to 1 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anode material for a lithium secondary battery and a method for producing the same, and more particularly to an anode material for a lithium secondary battery having improved reversibility, which contains carbon nanotubes protruding from the outside of the anode material, and a method for producing the same. [Background technology]

[0002] Lithium-ion batteries are the secondary battery system most widely used today, from portable electronic communication devices and electric vehicles to energy storage devices. Compared to commercial aqueous secondary batteries (Ni-Cd, Ni-MH, etc.), lithium-ion batteries have been attracting attention due to their advantages such as high energy density, operating voltage, and relatively small self-discharge rate. However, when considering more efficient usage time in portable devices and improved energy characteristics in electric vehicles, improving electrochemical characteristics remains a technical problem to be solved. For this reason, a lot of research and development is currently underway on the four major raw materials, including the positive electrode, negative electrode, electrolyte, and separator.

[0003] Among these raw materials, graphite-based materials that show excellent capacity retention and efficiency have been commercialized for the anode. However, the relatively low theoretical capacity value (LiC6: 372mAh / g) and low discharge capacity ratio of graphite-based materials are somewhat insufficient to meet the high energy and high power density characteristics of batteries required by the market. Therefore, many researchers are interested in the IV group elements (Si, Ge, Sn) on the periodic table, and among them, Si in particular has attracted attention as a very attractive material due to its very high theoretical capacity value (Li15Si4: 3600mAh / g) and low operating voltage (~0.1V vs. Li / Li+). However, general Si-based anode materials have the disadvantage of being difficult to apply to actual batteries due to their volume change of up to 300% during cycling and low discharge capacity ratio characteristics.

[0004] To solve this problem, Chinese patent CN2006-10170615 (BYD) discloses that the performance can be improved by including carbon nanotubes in a composite material containing elemental silicon, graphite, and amorphous carbon, and Korean patent 10-0569188 discloses that the performance can be improved by applying carbon fibers such as VGCF to configure an electrode. In general, carbon nanotubes have excellent mechanical and electrical properties and are in the spotlight as an effective material for improving the structural stability and conductivity of Si anode materials. However, it is important to ensure that such carbon nanotubes and carbon fibers are uniformly dispersed in the material or electrode, and if this problem is not solved, there is a disadvantage that the provision of a high specific surface area causes a loss of electrical paths between the particles of the anode material, which leads to performance degradation.

[0005] Therefore, there is a need to develop a technology that can control the loss in the electrical path and solve the problem of degradation. Summary of the Invention [Problem to be solved by the invention]

[0006] The present disclosure aims to provide a negative electrode material with improved charge / discharge reversibility and expansion characteristics by adding linear carbon nanotubes, which have excellent mechanical strength and electrical conductivity, to a negative electrode material made of nanosilicon and carbon, thereby complementing the electrical conductivity of the nanosilicon through two-dimensional physical bonds with the nanosilicon inside the negative electrode material particles.

[0007] In addition, by forming carbon nanotubes protruding from the outside of the anode material, an electrical path is provided between the anode material particles, thereby providing an anode material that can minimize the amount of separate carbon nanotubes used when constructing a battery electrode. [Means for solving the problem]

[0008] According to one embodiment, the negative electrode material for a lithium secondary battery includes nanosilicon, crystalline carbon, amorphous carbon, and carbon nanotubes, one end of the carbon nanotubes is located inside the negative electrode material and the other end is protruding to the outside, and the average length of the carbon nanotubes protruding to the outside of the negative electrode material may be in the range of 0.1 μm to 1 μm.

[0009] In addition, the average length of the carbon nanotubes protruding from the negative electrode material may be in the range of 0.5% to 10% of the entire length of the carbon nanotubes.

[0010] The negative electrode material may further include carbon nanotubes located only inside the negative electrode material.

[0011] The content of the carbon nanotubes may be in the range of 0.25 wt % to 1.5 wt % based on the total weight of the crystalline carbon and amorphous carbon contained in the negative electrode material.

[0012] The specific surface area of ​​the negative electrode material is 4m 2 / g~5.0m 2 / g.

[0013] The amorphous carbon may be a coal-based pitch having a fixed carbon content of 70 wt% or more and a beta resin value of 25 or more, and the crystalline carbon may include one or more selected from natural graphite and artificial graphite.

[0014] A method for manufacturing a negative electrode material for a lithium secondary battery according to one embodiment of the present invention includes the steps of: mixing nanosilicon slurry, carbon nanotube slurry, and crystalline carbon to prepare a solution; spray-drying the solution to prepare a first precursor; mixing the first precursor and amorphous carbon, filling a mold, and carbonizing the mold after high-temperature pressurization to prepare a carbonized block; mixing and coating the prepared carbonized block with amorphous carbon to prepare a second precursor; and carbonizing and classifying the second precursor. The step of spray-drying the solution to prepare a first precursor may include a step of controlling an average particle size (D50) of the first precursor to a range of 8 μm to 30 μm.

[0015] In the step of controlling the size of the first precursor, the average particle size (D50) of the first precursor can be controlled to a range of 10 μm to 25 μm.

[0016] In the step of preparing a solution by mixing the nanosilicon slurry, the carbon nanotube slurry, and the crystalline carbon, the carbon nanotube content may be in the range of 0.25 wt% to 1.5 wt% based on the total weight of the crystalline carbon and amorphous carbon contained in the negative electrode material.

[0017] In the prepared negative electrode material for a lithium secondary battery, one end of the carbon nanotubes is located inside the negative electrode material and the other end is located protruding to the outside, and the average length of the carbon nanotubes protruding to the outside of the negative electrode material may be in the range of 0.1 μm to 1 μm.

[0018] In addition, the average length of the carbon nanotubes protruding from the negative electrode material may be in the range of 0.5% to 10% of the entire length of the carbon nanotubes. Effect of the Invention

[0019] According to the present disclosure, the negative electrode material includes carbon nanotubes dispersed throughout the interior and exterior, and the improved electrical conductivity of the nanosilicon within the negative electrode material and the improved contact between adjacent particles outside the negative electrode material can improve charge / discharge reversibility.

[0020] Therefore, the cycle life of a lithium ion battery to which the negative electrode material according to the present disclosure is applied can be improved. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a diagram showing an image of a negative electrode material including carbon nanotubes according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing an enlarged image of FIG. [Diagram 3] FIG. 4 is a diagram showing measurement results of electrical conductivity according to density of a first precursor according to an embodiment of the present invention. [Figure 4] FIG. 4 is a graph showing measurement results of electrical conductivity according to density of a negative electrode according to an embodiment of the present invention. [Diagram 5] FIG. 13 is a graph showing the measurement results of recovery voltage after the end of discharge versus the amount of carbon nanotubes added. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, a first part, component, region, layer or section described below can be referred to as a second part, component, region, layer or section without departing from the scope of the present invention.

[0023] The terminology used herein is for the purpose of referring to specific embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. As used herein, the meaning of "comprising" is intended to embody certain properties, regions, integers, steps, operations, elements and / or components, and does not exclude the presence or addition of other properties, regions, integers, steps, operations, elements and / or components.

[0024] When an item is described as being "on" or "above" another item, it may be on or above the other item, or it may have other items between them. In contrast, when an item is described as being "directly on" another item, there are no other items between them.

[0025] Moreover, unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight.

[0026] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted as having a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted in an ideal or very formal sense unless defined.

[0027] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described in detail, but they are presented by way of example only and are not intended to limit the present invention, which is defined only by the scope of the claims that follow.

[0028] FIG. 1 is a diagram showing an image of an anode material including carbon nanotubes according to one embodiment of the present invention, and FIG. 2 is a diagram showing an enlarged image of FIG.

[0029] Specifically, FIG. 2(a) is an enlarged image of a portion of the carbon nanotubes in FIG. 1(a), and FIG. 2(b) is an enlarged image of a portion of the carbon nanotubes in FIG. 1(b).

[0030] With reference to FIG. 1 and FIG. 2, a negative electrode material for a lithium secondary battery according to one embodiment of the present invention will be described.

[0031] Referring to FIG. 1, an embodiment of the negative electrode material for a lithium secondary battery according to the present invention may include nanosilicon, crystalline carbon, amorphous carbon, and carbon nanotubes.

[0032] The nanosilicon (nano-Si) may be MG-Si or poly-Si. The nanosilicon may be included in the range of 45wt% to 50wt% of the total weight of the negative electrode material for lithium secondary batteries. If the content of the nano-Si is higher than the range, the nano-Si and graphite for imparting conductivity and reversibility cannot be completely captured in the high-density pitch carbon layer described below. This also results in the side effect that the above-mentioned properties of the nano-Si cannot be confirmed and the structure collapses. On the other hand, if the content of the nano-Si is lower than the range, there is a problem that it is difficult to achieve high capacity of the Si-carbon composite negative electrode material.

[0033] The carbon nanotubes may be included in the range of 0.1wt% to 1.5wt% of the total weight of the crystalline carbon and amorphous carbon included in the anode material, specifically, 0.25wt% to 1.25wt%. If the carbon nanotube content is lower than the above range, the carbon nanotubes may not be sufficiently distributed inside and outside the anode material, and may not be able to sufficiently complement the conductivity of the nanosilicon inside and provide an electrical path between the particles of the anode material. If the carbon nanotube content is higher than the above range, there is a problem of increased raw material costs. In addition, due to the low density of the carbon nanotubes, it is difficult to form a pitch-based high-density carbon layer, and there is a possibility that a problem of increased electrolyte side reactions due to the increase in the specific surface area of ​​the anode material may occur. In addition, there may be a problem of decreased lifespan and poorer characteristics of nano-Si being captured by the pitch-derived carbon layer, leading to poorer expansion characteristics.

[0034] The carbon nanotubes may have a diameter of less than 20 nm, specifically, in the range of 5 nm to 10 nm. When the diameter of the carbon nanotubes is in the above range, the carbon nanotubes can have suitable mechanical properties, which is advantageous for pulverization and dispersion.

[0035] At this time, the average length of the carbon nanotubes protruding from the negative electrode material may be in the range of 0.05 μm to 1.2 μm, specifically, in the range of 0.1 μm to 1 μm. When the average length of the protruding carbon nanotubes is in the above range, it is advantageous to effectively provide an electrical path between the negative electrode materials.

[0036] In addition, the average length of the carbon nanotubes protruding outside the negative electrode material may be in the range of 0.25% to 12% of the entire nanotube length, specifically, in the range of 0.5% to 10%.

[0037] If the average length of the carbon nanotubes protruding from the negative electrode material is shorter than the above range, the effective contact between the particles may decrease, and the electrical path between the particles may not be effectively provided. Also, if the average length of the carbon nanotubes protruding from the negative electrode material is longer than the above range, the length of the carbon nanotubes protruding from the negative electrode material may be too long, which may increase the specific surface area of ​​the negative electrode material and reduce its performance.

[0038] Meanwhile, the length of the carbon nanotubes protruding from the negative electrode material can be observed and measured through TEM analysis. The average length of the carbon nanotubes protruding from the negative electrode material can be calculated as an average length of 10 or more carbon nanotubes protruding from the negative electrode material measured through TEM analysis.

[0039] In addition, the average particle size (D50) of the negative electrode material excluding the carbon nanotubes protruding out of the negative electrode material may be in the range of 10 μm to 20 μm. If the average particle size (D50) of the negative electrode material excluding the carbon nanotubes protruding out of the negative electrode material is smaller than the above range, the length of the carbon nanotubes protruding out of the negative electrode material becomes too long, which may cause a problem of increasing the specific surface area of ​​the negative electrode material and decreasing performance. In addition, if it is smaller than the above range, the number of particles increases per the same part by weight, making it difficult to form a high-density support layer based on amorphous carbon, which may cause a problem of decreasing performance.

[0040] In addition, the density of the negative electrode material according to one embodiment of the present invention is 0.5 g / cm 3 ~1.0g / cm 3 It can be in the range of 0.6 g / cm 3 ~0.9g / cm 3 The range can be:

[0041] In addition, the negative electrode material according to one embodiment of the present invention has a thickness of 4m 2 / g~5.0m 2 The specific surface area can be in the range of 1 / g.

[0042] If the specific surface area of ​​the negative electrode material, as measured by the BET method, is larger than the above range, it will provide a side reaction site with the electrolyte, leading to a decrease in capacity. On the other hand, if the specific surface area is smaller than the above range, the wetting of the negative electrode material particles with the electrolyte will decrease, which may cause a problem of a decrease in the electrochemical activation rate.

[0043] The crystalline carbon may include at least one selected from natural graphite and artificial graphite. In this case, the graphite can be used to impart electrical conductivity and reversibility. When the graphite is scaly graphite, it may be added in a composition of less than 50wt% within a range of 50wt% to 55wt% excluding the nano-Si content. The reason is to induce effective capture, as described above.

[0044] The amorphous carbon may be a coal-based pitch, the fixed carbon content of which may be, for example, 50 wt% or more, more specifically, in the range of 60 wt% to 80 wt%.

[0045] As the fixed carbon content of the coal-based pitch increases, a conductive path is formed with Si, which has low self-conductivity, leading to increased capacity and efficiency. When the fixed carbon content is within the above range, the internal porosity of the anode material of the present embodiment can be reduced. This can also reduce side reactions with the electrolyte, contributing to an increase in the initial efficiency of the battery.

[0046] The coal-based pitch may have a β-resin value of, for example, 22 or more, more specifically, in the range of 25-40 or 25-35.

[0047] Specifically, the beta-resin value means a value obtained by subtracting quinoline capacity from benzene-insoluble capacity. Such a beta-resin value is proportional to caking property. In the present embodiment, since the coal-based pitch having a beta-resin value satisfying the above range is included, the structure of the anode material can be more stably maintained. Therefore, when the anode material according to the present embodiment is applied, a lithium ion battery having excellent life characteristics and plate expansion characteristics can be realized.

[0048] The negative electrode material according to an embodiment of the present invention can be prepared by the following method.

[0049] First, zirconia beads were used to nano-pulverize silicon by mechanical milling. The raw material particle size was applied at the same size, and the zirconia beads were used at a size less than twice the D99 of the input raw material. If the particle size D99 is too large or the zirconia beads are small, the nano-ization efficiency may be excessively reduced, the time required for nano-ization may increase, and side effects such as oxidation of silicon may occur. In this case, 99.9% pure anhydrous ethanol was used as the solvent to prevent oxidation of silicon particles, and the solid content ratio was in the range of 8 to 15% for effective nano-ization. The BPR (ball to powder ratio) of the raw material to the zirconia beads was 5:1, and the rotation speed of the rotor inside the mill was maintained at 2500 rpm in all examples.

[0050] Carbon nanotubes in a range of 0.25wt% to 1.5wt% of the mixture weight ratio of coal-based pitch, which is a raw material of crystalline carbon and amorphous carbon, were linearly dispersed in 99.9% purity anhydrous ethanol and mixed with the nanosilicon slurry. Crystalline carbon can be additionally mixed in. The carbon nanotube content can be mixed in a range of 0.25wt% to 1.5wt% of the total weight of crystalline carbon and amorphous carbon contained in the anode material.

[0051] Then, the first precursor is obtained in a powder state using a spray dryer. At this time, the method may include a step of controlling the size of droplets during spray drying using the spray dryer. That is, the method may include a step of controlling the size of the first precursor. The average particle size (D50) of the first precursor may be controlled in the range of 8 μm to 30 μm, specifically, in the range of 10 μm to 25 μm. The size of the droplets of the first precursor may be controlled by adjusting the amount of slurry injected, the rotation speed of the disk, the size of the spray nozzle, etc. However, it is not limited thereto. When the size of the droplets of the first precursor is within the above range, the protruding length of the carbon nanotubes protruding outside the negative electrode material can be efficiently controlled. When the average particle size (D50) of the first precursor is smaller than the above range, the length of the carbon nanotubes protruding outside the negative electrode material is too long, which may cause a problem of increasing the specific surface area of ​​the negative electrode material and reducing performance. In addition, if the average particle size (D50) of the first precursor is larger than the above range, the length of the carbon nanotubes protruding from the negative electrode material becomes too short, resulting in a decrease in effective contact between particles of the negative electrode material and an inability to effectively provide an electrical path between the particles.

[0052] The first precursor is placed in a mold and compressed at 2 ton / cm 2 The following pressures can be applied:

[0053] This makes it possible to control the specific surface area of ​​the first precursor, control the density, and prepare for the production of a negative electrode material, which is the object of the present invention and will be described later.

[0054] In this case, the crystalline carbon may be scaly graphite or artificial graphite, and preferably, graphite having a size smaller than the median particle size of the precursor based on the median particle size D(50) may be used, and specifically, the particle size of the graphite may be in the range of 5 μm to 10 μm. Generally, silicon, particularly nano-pulverized silicon, has a very low electrical conductivity of the powder due to the low electrical conductivity of silicon itself and surface oxidation.

[0055] The spray-dried precursor composed of nano-Si-graphite obtained in this way can be completely bound to the nano-Si-graphite precursor by forming a carbon support layer in the final product. The milling process can be performed using a process that uses a powder contact medium such as mechanofusion or ball mill. Then, a process of applying a specific pressure for a specified time period is applied to minimize the pores inside the nano-Si-graphite precursor. The mixed coal-based pitch during the pressurization process can improve the electrochemical properties of the negative electrode powder formed by filling the fine pores inside the first precursor produced by the spray-drying process. The pressurization was performed by filling the powder into a self-made mold and using a pressurizing press. At this time, the shape of a block is determined by the pressurization.

[0056] After the pressure molding process, the block was carbonized in an inert atmosphere at less than 1000°C, then crushed using a JET mill, Pin mill, or other milling process, and then a coating process was applied in which a carbon source such as petroleum pitch or coal tar, PAA, or PVA, which has a softening point of less than 250°C, was evenly dispersed on the surface of the crushed particles. The coating process was performed using a twisted blade mixer, and process variables include time and rotation speed, but detailed explanations will be omitted in this invention. Then, the block was heat-treated in an inert atmosphere at a temperature of less than 1000°C, and the final product was produced by sieving.

[0057] In addition, the length of the carbon nanotubes protruding from the negative electrode material prepared according to the embodiment of the present invention can be observed and measured through TEM analysis. The average length of the carbon nanotubes protruding from the negative electrode material can be calculated as the average length of 10 or more carbon nanotubes protruding from the negative electrode material measured through TEM analysis. EXAMPLES

[0058] Hereinafter, the present invention will be described in detail with reference to examples, which are presented by way of example only and are not intended to limit the present invention, which is defined only by the scope of the claims set forth below.

[0059] Example 1 Nanosilicon with an average particle size D(50) of about 100 nm was produced by mechanical milling using silicon raw material. The produced nanosilicon-containing slurry was mixed with a slurry in which carbon nanotubes were linearly dispersed, and graphite particles were added and dispersed using a high-speed mixer to form a mixed slurry.

[0060] At this time, nanosilicon was mixed at 50wt% of the final product anode material, and carbon nanotubes were added at a content of 1.0wt% based on the weight of carbon contained in the anode material. The average particle size D(50) of the added graphite particles was similar to the average particle size D(50) of the first precursor obtained in the spray drying step described below.

[0061] Thereafter, the mixed slurry is spray-dried to synthesize a first precursor having an average particle size D(50) of about 8 um.

[0062] After mixing the first precursor and the coal-based pitch powder, the first precursor and the coal-based pitch powder were loaded into a mold of a specific size to form a carbon support for the powder, and the powder was subjected to a pressure of 50 ton / cm 2 The mixture is subjected to uniaxial pressing for 10 minutes at a pressure of 0.015g / cm2.

[0063] The block obtained from the pressure molding process was heat-treated in an inert atmosphere at less than 1000℃ to prevent oxidation of the nanosilicon, then crushed to a range of 10~15um based on D50 using a JET mill, and the same amount of coating material in the range of 5~10wt% of the nanosilicon input was added and stirred for about 30 minutes using a twisted blade mixer, and then heat-treated in an inert atmosphere at less than 1000℃, and finally sieved through #635mesh (20um) to obtain anode material products containing carbon nanotubes protruding from the outside.

[0064] The lengths of the final anode material and the carbon nanotubes protruding from the anode material were observed and measured through TEM analysis to obtain an average length of the carbon nanotubes protruding from the anode material. Specifically, the average length of 10 or more carbon nanotubes protruding from the anode material measured through TEM analysis was calculated.

[0065] The images of the multiples are shown in Figures 1 and 2.

[0066] Example 2 A negative electrode material was prepared in the same manner as in Example 1, except that the carbon nanotube content was different from the carbon content in the negative electrode material.

[0067] Comparative Examples 1-2 A negative electrode material was prepared in the same manner as in Example 1, except that the carbon nanotube content was different from the carbon content in the negative electrode material.

[0068] Comparative Examples 3 to 6 A negative electrode material was prepared in the same manner as in Example 1, except that the average length of the carbon nanotubes protruding from the outside of the negative electrode material was different.

[0069] Manufacturing Example The negative electrode materials manufactured in the above Experimental Examples 1-2 and Comparative Examples 1-6 were mixed with commercially available natural graphite to maintain the negative electrode capacity at 440mAh / g, and a test cell (coin half cell) was manufactured. The composition of the negative electrode was active material: conductive material: CMC: SBR = 95.8: 1: 1.7: 1.5, and the rolling density was maintained at 1.6g / cc. The electrolyte used for the life test was EC: EMC = 3: 7 (1.0M LiPF6) + VC 1.5wt%.

[0070] Test Example 1 First, the electrical conductivity was measured according to the density of the first precursor.

[0071] Approximately 10 g of the first precursor powder produced in Example 1 and Comparative Example 1 was placed in a container and heated at 2 ton / cm 2The pressurizing pressure was changed as follows, and pressurizing was performed for 1 minute at each pressure. The electrical conductivity of the first precursor pressurized to different densities according to the pressurizing pressure was measured. The electrical conductivity was measured using a powder resistance measuring device.

[0072] The results of measuring the electrical conductivity of the first precursor as a function of density are shown in Figure 3. The density of the first precursor was 0.6 g / cm 3 to about 1.2 g / cm 3 The resistance of the first precursor was measured while increasing the density of the first precursor to 0.8 g / cm. 3 It was found that the solubility of the carbon nanotubes increased rapidly after exceeding 100%. This was confirmed to be due to the addition of carbon nanotubes.

[0073] In the case of Comparative Example 1, 1.2 g / cm 3 This is believed to be due to the crystalline carbon in the first precursor. This confirms that the addition of carbon nanotubes can complement the conductivity of silicon.

[0074] The electrical conductivity was measured based on the density of the negative electrode material.

[0075] The electrical conductivity according to density of the negative electrode materials prepared in Example 1 and Comparative Example 1 was measured in the same manner as the electrical conductivity according to density of the first precursor.

[0076] The measurement results are shown in Figure 4.

[0077] In the case of Example 1, the electrical conductivity was higher than that of Comparative Example 1 at the same density, and it was found that the electrical conductivity improved as the density increased.

[0078] 1 and 2, the anode material according to Example 1 includes carbon nanotubes protruding not only inside but also outside the anode material. As the density increases, it can be seen that the protruding carbon nanotubes increase the conductivity of the anode material through physical bonding with adjacent particles.

[0079] Therefore, it can be seen that the added carbon nanotubes complement the conductivity of the nanosilicon inside the anode material and increase the overall conductivity through electrical connection with the surface of the adjacent anode material by protruding outside the anode material.

[0080] Test Example 2 The specific surface areas of the negative electrode materials according to Examples 1 and 2 and Comparative Examples 1 to 6 were measured.

[0081] The specific surface area was measured by the BET method using an ASAP2020 device manufactured by Micromeritics, by adsorbing / desorbing nitrogen gas.

[0082] The results of the specific surface area measurements are shown in Tables 1 and 2 below.

[0083] Test Example 3 For the test cells produced using the negative electrode materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2, the life characteristics after an initial charge / discharge test were evaluated by the following method.

[0084] In Table 1 below, the capacity (mAh / g) is obtained by manufacturing a CR2032 coin cell, charging at 0.1C 0.005V, with a 0.005C cut-off, and discharging at 0.1C 1.5V cut-off, and the efficiency (%) is obtained as the ratio of the discharge capacity to the 0.1C charge capacity.

[0085] The expansion (%) is obtained as the percentage increase in thickness of the charged electrode after 50 cycles at a current of 0.5 C relative to the initial electrode thickness.

[0086] Test Example 4 In Example 1 and Comparative Examples 1 to 4, the recovery voltage was measured after a rest period of 20 minutes had elapsed after the completion of discharge in the charge-discharge cycle, and the results are shown in FIG.

[0087] As the average protrusion length of the carbon nanotubes increased, an increase in the specific surface area was observed, and while there was no significant change in capacity efficiency, a decrease in lifespan due to the increase in specific surface area was observed. On the other hand, when there were no external protrusions, the specific surface area was the smallest, but the electrical contact ratio between the particles was low, resulting in the lowest lifespan characteristics, and it was confirmed that the expansion was at a similar level.

[0088] Referring to Tables 1 and 2 below, when the carbon content in the negative electrode material is 1.00 wt % and the average length of the carbon nanotubes protruding from the negative electrode material is 1 μm, the performance of the test cell using the negative electrode material according to the present invention is the best.

[0089] [Table 1]

[0090] [Table 2]

[0091] The present invention is not limited to the above-mentioned embodiment, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention belongs can understand that the present invention can be embodied in other specific forms without changing the technical idea or essential characteristics of the present invention. Therefore, the above-mentioned embodiment should be understood to be illustrative in all respects and not restrictive.

Claims

1. A negative electrode material for a lithium battery comprising nanosilicon, crystalline carbon, amorphous carbon and carbon nanotubes, One end of the carbon nanotube is located inside the negative electrode material, and the other end is protruding to the outside, The negative electrode material for lithium secondary batteries is characterized in that the average length of the carbon nanotubes protruding from the negative electrode material is in the range of 0.1 μm to 1 μm.

2. 2. The negative electrode material for lithium secondary batteries according to claim 1, wherein the average length of the carbon nanotubes protruding from the negative electrode material is in the range of 0.5% to 10% of the total length of the carbon nanotubes.

3. The negative electrode material for a lithium secondary battery according to claim 1 , further comprising carbon nanotubes located only inside the negative electrode material.

4. 2. The negative electrode material for lithium secondary batteries according to claim 1, wherein the carbon nanotube content is in the range of 0.25 wt % to 1.5 wt % based on the total weight of crystalline carbon and amorphous carbon contained in the negative electrode material.

5. The specific surface area of ​​the negative electrode material is 4 m 2 / g to 5.0 m 2 The negative electrode material for a lithium secondary battery according to claim 1 , wherein the content of the negative electrode material is in the range of / g.

6. 2. The negative electrode material for a lithium secondary battery according to claim 1, wherein the amorphous carbon is a coal-based pitch having a fixed carbon content of 70 wt % or more and a beta resin value of 25 or more.

7. The crystalline carbon is 2. The negative electrode material for a lithium secondary battery according to claim 1, comprising at least one selected from the group consisting of natural graphite and artificial graphite.

8. mixing the nano silicon slurry, the carbon nanotube slurry and the crystalline carbon to prepare a solution; spray drying the solution to produce a first precursor; mixing the first precursor and amorphous carbon into a mold, and then carbonizing the mixture after high-temperature pressing to prepare a carbonized block; Coating the carbonized block with amorphous carbon to prepare a second precursor; and carbonizing and classifying the second precursor; The step of spray-drying the solution to produce a first precursor includes a step of controlling an average particle size (D50) of the first precursor to be in the range of 8 μm to 30 μm.

9. In the step of controlling the size of the first precursor, The method for producing a negative electrode material for a lithium secondary battery according to claim 8, wherein the first precursor has an average particle size (D50) controlled in the range of 10 μm to 25 μm.

10. In the step of preparing a solution by mixing the nano silicon slurry, the carbon nanotube slurry, and the crystalline carbon, 9. The method of claim 8, wherein the carbon nanotube content is in the range of 0.25 wt % to 1.5 wt % based on the total weight of the crystalline carbon and amorphous carbon contained in the negative electrode material.

11. In the produced negative electrode material for lithium secondary batteries, One end of the carbon nanotube is located inside the negative electrode material, and the other end is protruding to the outside, 9. The method for producing an anode material for a lithium secondary battery according to claim 8, wherein the average length of the carbon nanotubes protruding from the anode material is in the range of 0.1 μm to 1 μm.

12. In the produced negative electrode material for lithium secondary batteries, One end of the carbon nanotube is located inside the negative electrode material, and the other end is protruding to the outside, The method for producing a negative electrode material for a lithium secondary battery according to claim 8, wherein the average length of the carbon nanotubes protruding from the negative electrode material is in the range of 0.5% to 10% of the total length of the carbon nanotubes.

Citation Information

Patent Citations

  • Negative electrode active material, electrochemical device, and electronic device

    CN112820869A

  • Anode active material for lithium secondary battery and lithium secondary battery comprising same

    EP3859834A1

  • Nonaqueous electrolyte secondary battery and its negative electrode

    JP2006339092A

  • Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery using it

    JP2007188864A

  • Composite active material and electrochemical element using same

    JP2008166013A